2015
DOI: 10.1016/j.fertnstert.2015.07.1166
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive carrier genetic test using next-generation deoxyribonucleic acid sequencing in infertile couples wishing to conceive through assisted reproductive technology

Abstract: We have developed a comprehensive carrier genetic screening test that, combined with our matching system and genetic counseling, constitutes a powerful tool to avoid more than 600 mendelian diseases in the offspring of patients undergoing ART.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
61
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(62 citation statements)
references
References 28 publications
1
61
0
Order By: Relevance
“…Some of these recent applications of GT include presymptomatic/ predictive testing of healthy individuals for susceptibility to develop a disease later in life, pharmacogenomic and nutrigenomic GT aimed at optimizing medical treatment and diet, respectively, based on one's genetic makeup (National Institutes of Health, 2010;Collins et al, 2014). Moreover, recent developments in human genetics have revolutionized GT for reproductive purposes, such as through carrier screening for monogenic recessive disorders, where individuals or couples can now be tested for the carrier status of hundreds of recessive conditions that may affect their children (Srinivasan et al, 2010;Martin et al, 2015;Nazareth et al, 2015;Silver et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Some of these recent applications of GT include presymptomatic/ predictive testing of healthy individuals for susceptibility to develop a disease later in life, pharmacogenomic and nutrigenomic GT aimed at optimizing medical treatment and diet, respectively, based on one's genetic makeup (National Institutes of Health, 2010;Collins et al, 2014). Moreover, recent developments in human genetics have revolutionized GT for reproductive purposes, such as through carrier screening for monogenic recessive disorders, where individuals or couples can now be tested for the carrier status of hundreds of recessive conditions that may affect their children (Srinivasan et al, 2010;Martin et al, 2015;Nazareth et al, 2015;Silver et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Until now, particularly targeted, gene panel-based, nextgeneration sequencing approaches have been described. 2,[7][8][9] An approach using targeted analysis after untargeted whole-exome sequencing (WES) has been explored in one study that filtered for identical mutations in approximately 500 genes in both partners of four consanguineous couples. 10 However, systematic assessment of the use of WES for PCS has not been performed so far.…”
Section: Introductionmentioning
confidence: 99%
“…Of 3738 couples (6643 individuals) screened, 25.1% of individuals were found to carry at least one pathogenic mutation, and eight (0.21%) of the couples were found to be carriers of the same genetic conditions not detectable by existing screening programmes. In their study, Martin et al . found that 5% of couples were carriers of the same genetic disease which affected reproductive choices.…”
Section: Disclosure Of Interestsmentioning
confidence: 99%
“…The majority (76.7%) of these mutations were not covered (and would have been missed) by traditional ACOG screening guidelines. In another study, Martin et al . reported the use of next‐generation sequencing‐based ECS of 549 recessive and X‐linked genetic conditions of 2570 infertile couples undergoing assisted reproductive technology.…”
Section: Disclosure Of Interestsmentioning
confidence: 99%